2010
DOI: 10.1016/j.marenvres.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, thermally-induced shifts in species distribution range in the Humboldt current upwelling system

Abstract: a b s t r a c tEl Niño-Southern Oscillation (ENSO) is a global climate variablility, which fundamentally influences environmental patterns of the Humboldt Current System (HCS) off Chile and Peru. The surf clams Donax obesulus and Mesodesma donacium are dominant and highly productive bivalves of exposed sandy beaches of the HCS. Existing knowledge indicates that El Niño (EN, warm phase of ENSO) and La Niña (LN, cold phase of ENSO) affect populations of both species in a different way, although understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…In this vein, mass M. donacium mortalities that occurred during strong warm ENSO events have been mainly associated with rising temperatures and increasing susceptibility to parasitism and diseases under anomalous environmental conditions (Arntz et al 1987, Ibarcena et al 2005, Riascos et al 2009. These mass mortalities, which mainly occurred at the northernmost bioclimatic unit, generated drastic changes in the ecosystem and in the macrofaunal community structure, including increasing densities of subordinate competitors, such as the clam Donax obesulus (Arntz et al 1987, Carstensen et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, mass M. donacium mortalities that occurred during strong warm ENSO events have been mainly associated with rising temperatures and increasing susceptibility to parasitism and diseases under anomalous environmental conditions (Arntz et al 1987, Ibarcena et al 2005, Riascos et al 2009. These mass mortalities, which mainly occurred at the northernmost bioclimatic unit, generated drastic changes in the ecosystem and in the macrofaunal community structure, including increasing densities of subordinate competitors, such as the clam Donax obesulus (Arntz et al 1987, Carstensen et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…These mass mortalities have been attributed to a number of factors, namely positive sea temperature anomalies, harmful algal blooms, environmental stress, parasitism, and storms (Odebrecht et al 1995, Fiori et al 2004, Riascos et al 2009, Carstensen et al 2010). In the case of M. mactroides, it has been suggested that the effect of these mortalities may swamp management measures (Defeo 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Along the central-south coast of Peru and northern Chile, permanent upwelling changes only incrementally in magnitude during the austral spring and summer (Echevin et al, 2008;Thiel et al, 2007). This pattern contrasts with the strong seasonal upwelling changes in other coastal regions located at the northern (~3°S) and southern (~36°S) extremes of this ecosystem (Chavez et al, 2008;Thiel et al, 2007), and with other coastal systems at similar latitude (Carstensen et al, 2010;Uribe et al, 2012). Seasonal variability in the structure of invertebrate assemblages in this ecosystem appears habitat specific.…”
Section: Introductionmentioning
confidence: 55%
“…En la zona norte de Chile y sur de Perú en particular, la desaparición de grandes poblaciones de macha ha coincidido con la ocurrencia de eventos El Niño intensos (Riascos et al, 2008;Carstensen et al, 2010), con aumentos en la temperatura superficial del mar y disminuciones en salinidad al norte de los 30°S. El rango de distribución de la macha entre los 5°N y la isla de Chiloé (Tarifeño, 1980), se redujo en su extremo norte en cerca de 20° (Arntz et al, 1987) [1982][1983], mientras que durante El Niño 1997-1998 importantes poblaciones de Arica (~18°S) y Coquimbo (~29°55'S) fueron diezmadas, para posteriormente recuperarse (Aburto & Stotz, 2003;Stotz et al, 2005).…”
Section: Mesodesma Donacium Y Variabilidad Ambientalunclassified